2009
DOI: 10.1007/978-1-59745-204-5_21
|View full text |Cite
|
Sign up to set email alerts
|

Fungal and Bacterial Killing by Neutrophils

Abstract: Neutrophils are professional phagocytes of the innate immune system that are essential to control bacterial and fungal infections. These cells engulf and kill invading microbes. Additionally, activated neutrophils are able to release neutrophil extracellular traps (NETs). These fibers consist of chromatin decorated with antimicrobial proteins to trap and kill microbes. Appropriate quantitative methods are required to understand the nature of interactions of neutrophils with pathogens. Here we present assays to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 21 publications
1
60
0
7
Order By: Relevance
“…Other investigators have shown that NETs are capable of trapping and killing extracellular pathogens (12,27,28,31,34,52,64). Using fluorescein-labeled M. haemolytica cells, we found that bacterial cells were trapped, in a time-dependent manner, by NETs (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…Other investigators have shown that NETs are capable of trapping and killing extracellular pathogens (12,27,28,31,34,52,64). Using fluorescein-labeled M. haemolytica cells, we found that bacterial cells were trapped, in a time-dependent manner, by NETs (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…Human neutrophils were isolated from blood obtained from the blood bank in a protocol approved by the ethics committee of the CharitĂ© Hospital (Berlin, Germany). Neutrophils were purified by Histopaque/Percoll (68). After isolation, neutrophils were resuspended in Hanks balanced salt solution (Gibco) containing cations supplemented with 5% FCS and seeded at 7.5 × 10 4 neutrophils per well in a 96-well plate and allowed to rest for 30 min.…”
Section: Recovery Of Lps From Intracellular Bacteria and Preparation mentioning
confidence: 99%
“…4). Bacterial killing dependent on netosis, considered as the DNase-sensitive mechanism on activated cells, was calculated as previously reported (24) from CFU values obtained with PMA-stimulated cells treated and not treated with DNase. Netosis accounted for 18.0% Ïź 4.1% of WT C1845 bacterial killing by PLB-985 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of bacterial killing by netosis was determined as previously reported (24), considering the number of bacteria recovered after challenge of PMA-stimulated cells versus the number recovered after challenge of PMA-DNase-treated cells, as follows: [(df Ï« CFU with DNase ÏȘ df Ï« CFU with no DNase)/df Ï« CFU DNase] Ï« 100, where df is the dilution factor and CFU represents numbers of CFU.…”
Section: Reagents and Antibodies Nn-dimethyl Formamide (Dmf) Was Frommentioning
confidence: 99%